Automatic tuning of communication protocols for vehicular ad hoc networks using metaheuristics. - Toutouh-el-Alamin, Jamal; García-Nieto, José Manuel; Alba-Torres, Enrique (Elsevier, 2010)
The emerging field of vehicular ad hoc networks (VANETs) deals with a set of communicating vehicles which are able to spontaneously interconnect without any pre-existing infrastructure. In such kind of networks, it is crucial to make an optimal configuration of the communication protocols previously to the final network deployment. This way, a human designer can obtain an optimal QoS of the network beforehand. The problem we consider in this work lies in configuring the File Transfer protocol Configuration (FTC) with the aim of optimizing the transmission time, the number of lost packets, and the amount of data transferred in realistic VANET scenarios. We face the FTC with five representative state-of-the-art optimization techniques and compare their performance. These algorithms are: Particle Swarm Optimization (PSO), Differential Evolution (DE), Genetic Algorithm (GA), Evolutionary Strategy (ES), and Simulated Annealing (SA). For our tests, two typical environment instances of VANETs for Urban and Highway scenarios have been defined. The experiments using ns- 2 (a well-known realistic VANET simulator) reveal that PSO outperforms all the compared algorithms for both studied VANET instances.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/4626?template=romeo
Keywords: Redes de ordenadores; Programación heurística; Optimización matemática; Vehicular ad hoc networks; Optimal file transfer configuration; Metaheuristics; ns-2 simulator; Opitmization algorithm